Employability skills expected of polytechnic engineering students as it relates to technical and vocational education in Nigeria - Ojonugwa, Oguche Innocent; Hamzah, Ramlah; Bakar, Ab. Rahim; Mat Rashid, Abdullah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Polytechnic is one of the Technical and Vocational Education (TVET) institutions in Nigeria students graduate annually from the various polytechnics located within the country. As this number continue to rise significantly unemployment rate also increases. There is the need there, for polytechnic engineering students to acquire employability skills that will make them marketable and be gainfully employed and fit into the 21st century workforce. This study aims to identify the employability skills among the polytechnic engineering students in Nigeria. The research instrument used was a questionnaire adapted from the Secretary's Commission on Achieving Necessary Skills (SCANS) which consists of twenty four items. The employability skills surveyed include Basic skills, Thinking skills, foundation skill, competency: resource management, interpersonal skills, System skills and Technology skills. The instrument was distributed to 600 polytechnic engineering students. About 580 were appropriately filled and returned, giving a response rate of 96.67%. Majority of the participants 43.3% were students of Mechanical Engineering, Based on the survey, the three top most highly rated skills are, interpersonal skills, thinking and resource management skills with the same mean rating, and basic and personal skills came third with the same mean, Basic job performance skills were score above moderate level providing room for appropriate training to prepare students for future employment.